Knowledge and Perceptions of House Officers about Adopting Anesthesia Specialty (Medical Forum Monthly, 2024)
Objective: The study objective was to describe Knowledge and perceptions of house officers about adopting anesthesia specialty Methods Prior ethical approval was taken from institutional review boardStudy Design: descriptive quantitative cross-sectionalPlace and Duration of Study: This study was conducted at the Kishwar Fazal Teaching Hospital Lahore in six months time period from May 23, 2023 to October 23, 2023.Methods: House officers with one month experience were included. After their consent for study was obtained, 22 boys (44.89%) and 11 girls (22.44%) out of 49 house officers filled out self reporting survey questionnaire1 which made response rate 67.34% percent.Results: Out of 33 house officers, 22 (44.89%) considered Endo-tracheal intubation and specific expertise of spinal anesthesia as the most enjoyed portion of the house job. 23 (69.69%) believed that anesthetist enjoys a similar role in operations as a surgeon.Conclusion: House officers of anesthesia have positive perceptions about the field of anesthesiology serving as an inspiration for their juniors to adopt it which may help to counter workforce crises in this field.